The Role of Accounting Information Systems in Improving the Sustainability of Consumer Cooperatives in KPRI Sehat Rembang - Laiyinatul Azizah; Agustina Eka Harjanti; Heni Risnawati (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study examines the role of Accounting Information Systems (AIS) in supporting the sustainability of consumer cooperatives at KPRI SEHAT Rembang. Research Method: A descriptive qualitative approach was employed. Data were collected through interviews, observation, and documentation involving the cooperative’s chairman, treasurer, and employees. The data were analyzed using data reduction, data display, and conclusion drawing, with triangulation applied to ensure validity. Results and Discussion: The findings indicate that KPRI SEHAT Rembang has implemented an AIS based on Microsoft Excel to record transactions, manage savings and loans, and prepare financial statements. Although the system remains relatively simple and semi-manual, it has been applied consistently and provides financial information to support administrative activities, reporting, SHU calculation, and managerial decision-making. Implications: The study suggests that even a simple AIS can strengthen financial management practices and contribute to cooperative sustainability. Further research may explore the effectiveness of more integrated digital accounting systems in improving cooperative performance.